1943
DOI: 10.1177/00220345430220060601
|View full text |Cite
|
Sign up to set email alerts
|

The Citrate Content of Whole Teeth, Dentin and Enamel

Abstract: For a long time it has been appreciated that citrate is a constituent of milk and urine. With the development of more accurate and specific methods (1, 2) for the determination of citrate, this ion has been recognized as a constituent of many tissues and body fluids. The occurrence of citrate in the animal body has been reviewed by Smith and Orten (3). Scherst6n (4) has shown that there is quite a large amount of citrate in semen and in the secretion of the seminal vesicles, the concentration in semen being as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1953
1953
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…This dry weight value is highly consistent with the findings for human dentin. 35,37,39,42 For example, Zipkin and Gold 37 reported mean citrate content of 0.88% for 194 samples of human dentin. The only published data on citrate content of human cementum appear to be those of Brudevold et al, 24 who report dry weight values from 0.70-0.80%.…”
Section: B Fluoridementioning
confidence: 99%
See 1 more Smart Citation
“…This dry weight value is highly consistent with the findings for human dentin. 35,37,39,42 For example, Zipkin and Gold 37 reported mean citrate content of 0.88% for 194 samples of human dentin. The only published data on citrate content of human cementum appear to be those of Brudevold et al, 24 who report dry weight values from 0.70-0.80%.…”
Section: B Fluoridementioning
confidence: 99%
“…In teeth the citrate content of human permanent enamel is about 0.1% 35 37 and of dentin about 0.9% [35][36][37]38 on a dry, fat-free basis. Data on fluoride-citrate relationships in teeth appear to be limited and equivocal.…”
mentioning
confidence: 99%
“…The typical concentration of citrate in bone ranges from ~20–100 μmols/gram (micromoles/gram tissue weight); as compared to most other tissues in which the citrate concentration is ~0.2–0.4 normalμmols/gram [3, 4]. When adjusted for tissue water content (Table 1), bone contains ~25–75 fold higher citrate than most other tissues.…”
Section: Status Of Citrate In the Composition And Structure Of Bonementioning
confidence: 99%
“…In 1943, Free [ 4 ] reported that animal and human teeth and periodontal tissue contained high citrate levels; due to the high citrate concentrations in dentin and cementum. In contrast, enamel contains low citrate concentration.…”
Section: Status Of Citrate In the Composition And Structure Of Teethmentioning
confidence: 99%
See 1 more Smart Citation